How does Quality Management affect Customer Satisfaction in Educational Institutions? - Arina Santi; Ranto Setiyono; Azainil Azainil (Edumaspul: Jurnal Pendidikan, 2024)
This study aims to evaluate the influence of management in Indonesia and the implications on customer satisfaction in educational institutions with a special focus on the Special Region of Yogyakarta. The research method used is descriptive quantitative and qualitative approach. Data were collected from the Central Bureau of Statistics (BPS), the Ministry of Education and Culture, and relevant previous research results. Quantitative data included education indicators such as teacher education levels, education facilities and education outcomes. Qualitative data was obtained from a literature review on quality management and customer satisfaction in the education sector. The main findings of the study show that improving teachers' qualifications, reflected in the percentage of teachers who have at least a bachelor's degree, significantly contributes to improving teaching quality and student satisfaction. The analysis of education facilities revealed disparities between urban and rural areas in terms of access and quality of facilities. In addition, the results show that aspects such as teacher competence, service reliability and effective communication have a major influence on student satisfaction. The implications of this study are the importance of policies that focus on improving teachers' qualifications and competencies through continuous training programs, as well as improving educational facilities in underserved areas. In addition, educational institutions need to improve aspects of communication and responsiveness to better meet students' needs and expectations. The limitations of this study include the limited data available, especially in terms of qualitative data that could provide deeper insights into students' experiences. In addition, the study was limited to DIY and may not be fully representative of conditions across Indonesia. Further research is recommended to cover a wider area and use mixed methods to get a more comprehensive picture.